Enhanced Biodegradation of Long-chain Alkanes in Soils Using Matching Fenton Pre-oxidation. Issue 1 (2nd January 2020) - Du, Juan; Xu, Jinlan; Wang, Huifang; Li, Lu; Zhang, Shaofeng; Chen, Ziwei; Huang, Tinglin
ABSTRACT: The purpose of this study is to find matching Fenton pre-oxidation that can enhance the subsequent biodegradation of long-chain alkanes in soils. After matching Fenton pre-oxidation, the hydrocarbon degraders in soils grew quickly, which was stimulated to degrade the long-chain alkanes as its main carbon sources. Therefore, the long-chain alkanes removal was improved significantly. The results of this study suggested that the degradation of C25 – C30 after matching Fenton pre-oxidation was up to 5463 mg/kg (67%), which was 5.2 times higher than that of unmatching Fenton pre-oxidation (1044 mg/kg). In addition, after matching Fenton pre-oxidation, the hydrocarbon degraders were stimulated to degrade the long-chain alkanes and nitrogen sources hugely so that the hydrocarbon degraders can increase considerably (73%). This was the reason that the biodegradation of long-chain alkanes was enhanced by matching Fenton pre-oxidation.